Polyscias scutellaria Aqueous Leaves Extract Increases Insulin Levels and Improves Mammary Gland Histology in Lactating Rats - Budiono Budiono; Sumirah Budi Pertami; Kasiati Kasiati; Tutik Herawati; Nurul Pujiastuti; Siti Nur Arifah; Mochammad Fitri Atho'illah (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Exclusive breastfeeding could be a protective step to avoid infant stunting. During lactation, several hormones are involved in milk secretion, including insulin. Polyscias scutellaria is a perennial plant which has traditionally been used to increase breast milk production. This study was conducted to examine the impact of P. scutellaria leaf extract on the mammary gland histology, expression of insulin in the mammary gland, as well as plasma insulin and the insulin receptor levels.METHODS: Five female unmated rats (UR) and twenty female lactating rats were divided into five groups, namely UR, lactating rats only (LRO), lactating rats treated with Asifit (LRA), lactating rats treated with PSAE at a dosage of 250 and 500 mg/kg body weight (BW) (LRPSAE 250 and 500). Treatments were given orally for 14 days. The dams were sacrificed after the weaning stage (third week after parturition), and the serum, mammary gland, liver, and muscle were collected for further analysis.RESULTS: The histoarchitecture of mammary gland between the LRA and LRPSAE groups were similar. The LRPSAE 250 group had higher plasma level and immunofluorescent expression of insulin than the LRA group. PSAE did not affect insulin receptor beta subunit (INSR-β) levels in both liver and muscle of lactating rats.CONCLUSION: PSAE could be used as an herbal treatment to increase breast milk production by improving mammary gland histology and maintaining the mother's insulin levels.KEYWORDS: Polyscias scutellaria, lactating rats, insulin, INSR-β